THE PROGRESS OF MARKETING IN TOURISM INDUSTRY - Shaxobova Shaxzoda Avazovna (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. This essay aims to demonstrate the role that marketing plays in the growth and transformation of the global tourist sector. The business discipline of drawing tourists to a particular place is known as tourism marketing. Hotels, states, cities, tourist attractions, conference centres, and other places related to business and leisure travel all use fundamental marketing strategies to particular tactics aimed at boosting visitation.